2016
DOI: 10.1063/1.4941284
|View full text |Cite
|
Sign up to set email alerts
|

A parametric study for the generation of ion Bernstein modes from a discrete spectrum to a continuous one in the inner magnetosphere. II. Particle-in-cell simulations

Abstract: In this paper, we perform one-dimensional particle-in-cell simulations to investigate the properties of perpendicular magnetosonic waves in a plasma system consisting of three components: cool electrons, cool protons, and tenuous ring distribution protons, where the waves are excited by the tenuous proton ring distribution. Consistent with the linear theory, the spectra of excited magnetosonic waves can change from discrete to continuous due to the overlapping of adjacent unstable wave modes. The increase of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
49
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 38 publications
(55 citation statements)
references
References 10 publications
5
49
0
Order By: Relevance
“…For the chosen values of m p / m e and c / V A 0 , the proton gyrofrequency Ω p 0 = 0.01Ω e 0 and electron plasma frequency ω p e = 200Ω p 0 . The effects of using artificially lower values of c and m p / m e , which have been investigated thoroughly in Sun, Gao, Chen, et al () and Sun, Gao, Lu, et al (), reduce the lower hybrid resonance frequency ( ω LHR = Ω p ( m e / m p +( V A / c ) 2 ) −1/2 ) and thus tend to scale down the number of ion gyrofrequency harmonics excited as ω LHR is scaled down.…”
Section: Two‐dimensional Pic Simulation Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…For the chosen values of m p / m e and c / V A 0 , the proton gyrofrequency Ω p 0 = 0.01Ω e 0 and electron plasma frequency ω p e = 200Ω p 0 . The effects of using artificially lower values of c and m p / m e , which have been investigated thoroughly in Sun, Gao, Chen, et al () and Sun, Gao, Lu, et al (), reduce the lower hybrid resonance frequency ( ω LHR = Ω p ( m e / m p +( V A / c ) 2 ) −1/2 ) and thus tend to scale down the number of ion gyrofrequency harmonics excited as ω LHR is scaled down.…”
Section: Two‐dimensional Pic Simulation Modelmentioning
confidence: 99%
“…Satellite observations (Boardsen et al, ; Ma et al, ; Meredith et al, ; Min et al, ; Perraut et al, ) have shown a close relation between the excitation of magnetosonic waves and a ring‐like (or partial shell) distribution of tenuous energetic protons, and theoretical calculations (Chen, ; Chen, Thorne, Jordanova, & Horne, ; Curtis & Wu, ; Gul'elmi et al, ; McClements et al, ; Min & Liu, ; Sun, Gao, Chen, et al, ; Yuan et al, ) have verified that a proton ring distribution with the ring velocity V R comparable to the Alfven speed V A provides free energy to excite magnetosonic waves. The excitation of magnetosonic waves by a proton ring distribution in a uniform magnetized plasma has been thoroughly studied using 1‐D particle‐in‐cell (PIC) simulations (Chen et al, ; Liu et al, ; Sun, Gao, Lu, et al, ). The PIC simulations (e.g., Chen et al, ) show that the wave spectrum of the excited magnetosonic waves may change from discrete bands to continuous bands with the decrease of the wave normal angle or when the growth rate is sufficiently large.…”
Section: Introductionmentioning
confidence: 99%
“…Since MS waves were discovered several decades ago, a large number of studies, including theoretical works and particle‐in‐cell simulations, satellite observations, and statistical surveys, have been carried out to investigate the generation of MS waves. The results demonstrate that the background plasma and source particles are the two key factors to the wave generation [ Kennel , ; Chen et al ., ; Sun et al ., , , ]. Especially, a recent study, using detailed satellite data, has revealed that MS waves can be locally excited by protons with a ring distribution in velocity space [ Balikhin et al ., ].…”
Section: Introductionmentioning
confidence: 99%
“…PIC simulation has always been a powerful tool for analyzing plasma waves and instabilities (Decyk, 1995;Lu & Cai, 2001;Sun et al, 2016Sun et al, , 2017Sun et al, , 2019. A 2-D electrostatic PIC code with periodic boundary conditions is used in our simulations.…”
Section: Simulation Modelmentioning
confidence: 99%